2014
DOI: 10.1371/journal.pone.0093615
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual Dimorphism of Staminate- and Pistillate-Phase Flowers of Saponaria officinalis (Bouncing Bet) Affects Pollinator Behavior and Seed Set

Abstract: The sequential separation of male and female function in flowers of dichogamous species allows for the evolution of differing morphologies that maximize fitness through seed siring and seed set. We examined staminate- and pistillate-phase flowers of protandrous Saponaria officinalis for dimorphism in floral traits and their effects on pollinator attraction and seed set. Pistillate-phase flowers have larger petals, greater mass, and are pinker in color, but due to a shape change, pistillate-phase flowers have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 55 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…In one of the only other studies to date to examine sexual dimorphism in a sequentially hermaphroditic plant species, Davis et al () found that female‐phase flowers of Saponaria officinalis (Caryophyllaceae) have larger petals and are “pinker” in color than male‐phase flowers. However, due to a change in floral presentation, female‐phase flowers have smaller corolla diameters than male‐phase flowers and attract significantly fewer pollinators.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In one of the only other studies to date to examine sexual dimorphism in a sequentially hermaphroditic plant species, Davis et al () found that female‐phase flowers of Saponaria officinalis (Caryophyllaceae) have larger petals and are “pinker” in color than male‐phase flowers. However, due to a change in floral presentation, female‐phase flowers have smaller corolla diameters than male‐phase flowers and attract significantly fewer pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to a change in floral presentation, female‐phase flowers have smaller corolla diameters than male‐phase flowers and attract significantly fewer pollinators. Pollinators of S. officinalis prefer whiter (less pink) flowers independent of the presence of stamens, nectar volume, and flower size (Davis et al, ). A strong pollinator preference for the floral phenotype associated with male sexual function in S. officinalis supports the hypothesis that sexual dimorphism may result in features that promote male fitness more than female fitness in a bisexual flower (at least in S. officinalis ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations